PENGARUH REINFORCEMENT NEGATIF TERHADAP MOTIVASI BELAJAR IPA SISWA SD - Yulianti, Sandy; Putra, Jaya Adi; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack:This study aimed to determine the effect of negative reinforcement to increase learning motivation of fifth grade science students in elementary school. These transactions are carried out in primary research school 177 Pekanbaru on the class. The data collection method is using video shoot and questionnaire. The study was conducted 5 meetings 5 times in class VA and VB . In VA, the teacher used more the negative reinforcement rather than in VA. Moreover the result of motivation thet students have in VA higher than student in VB. The impact of the use of negative reinforcement learning motivation in class that raises false or not permanent and cause discomfort among students and teachers. To reduce it to the teachers should do more active learning more engaging students.Key Words: Negative reinforcement, learning motivation